2016
DOI: 10.3389/fmicb.2015.01564
|View full text |Cite
|
Sign up to set email alerts
|

Individual-Based Modeling of Tuberculosis in a User-Friendly Interface: Understanding the Epidemiological Role of Population Heterogeneity in a City

Abstract: For millennia tuberculosis (TB) has shown a successful strategy to survive, making it one of the world’s deadliest infectious diseases. This resilient behavior is based not only on remaining hidden in most of the infected population, but also by showing slow evolution in most sick people. The course of the disease within a population is highly related to its heterogeneity. Thus, classic epidemiological approaches with a top-down perspective have not succeeded in understanding its dynamics. In the past decade a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…These are firstly the Lipschitz criteria and secondly the stability analysis of the model with graphical analysis and phase space portraits. It is hoped that the proposed analysis and the results will aid mathematical biologists in conducting research in different domains where stochastic modelling is applicable [31][32][33][34][35][36][37][38][39][40][41][42]. Trends in current human settlement, together with rapidly expanded urban areas, exploding population density, and limited socio-economic resources, suggest that the human factors, in addition to climate factors are important components in understanding current and future risks of disease transmission [1,32].…”
Section: Discussionmentioning
confidence: 99%
“…These are firstly the Lipschitz criteria and secondly the stability analysis of the model with graphical analysis and phase space portraits. It is hoped that the proposed analysis and the results will aid mathematical biologists in conducting research in different domains where stochastic modelling is applicable [31][32][33][34][35][36][37][38][39][40][41][42]. Trends in current human settlement, together with rapidly expanded urban areas, exploding population density, and limited socio-economic resources, suggest that the human factors, in addition to climate factors are important components in understanding current and future risks of disease transmission [1,32].…”
Section: Discussionmentioning
confidence: 99%
“…The flow diagram, subprocess and sub models are shown in Figure 4, adapted from [10]. Some actions can only happen if some conditions are fulfilled.…”
Section: Methodsmentioning
confidence: 99%
“…These additional testing sites increased TB case detection by 92%, with 65% of patients referred for appropriate treatment operational in Nigeria. These additional testing sites increased TB case detection by 92%, with 65% of patients referred for appropriate treatment [10] ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Ahmad and Billimek (2005) developed a system dynamics model which analyzes policies to reduce the harmful effects of tobacco on population health. Saysel et al (2002) Prats et al (2016) showed how discrete-event models can be used to evaluate public policies in the transmission of tuberculosis in big cities. Eubank (2002) and Rao and Chernyakhovsky (2008) showed with their development of specialized simulation tools that parallel discrete-event simulation was required for large-scale epidemiological models.…”
Section: Related Workmentioning
confidence: 99%